Perancangan Aplikasi Panduan Digital Sebagai Layanan Dan Informasi Masjid Berbasis Mobile( Studi Kasus : Masjid Al-Bakrie Pt.Snp Jambi) - Maulana. Sidiq, M. Ade; Nugroho, Agus; Nugroho, Hendri (Jurnal Informatika Dan Rekayasa Komputer(JAKAKOM), 2024)
Utilization of technology and information systems has become a necessity for individuals and organizations. The dissemination of information at Al-Bakrie Mosque is still carried out manually, using a public address system, some of which are also damaged, and information dissemination is also done from person to person. Mosque cash recording is also still done manually, which is inefficient and prone to errors in information delivery and cash recording. To address these issues, an application has been developed to facilitate information dissemination, mosque cash recording, and other features such as prayer procedures, ablution procedures, prayer schedules, and short prayer guides for children. The method used for designing this application is the waterfall model, with UML tools including use case diagrams, activity diagrams, and class diagrams. The application is developed using the Flutter Dart programming language and MySQL database. This mobile-based application can assist mosque administrators in managing mosque information dissemination. Keywords: Design; System; System Design; Application; Information; Mosque